The application of the microalgae Chlorella spp. as a supplement in broiler feed. Issue 2 (5th April 2019) - ABDELNOUR, S.A.; ABD EL-HACK, M.E.; ARIF, M.; KHAFAGA, A.F.; TAHA, A.E.
Abstract : Chlorella ( vulgaris spp. ; CLV) is a genus of unicellular freshwater microalgae that are fit for human consumption and are used as additives with high nutritional value in feed for agriculturally important animals. Chlorella spp. are characterised by their simple cultivation, high productivity and levels of protein and other nutrients. Investigations have shown that the growth performance of broilers can be positively affected by the addition of very low amounts of CLV biomass (0.5-1.0% of the diet) to feed. The effect of CLV on growth and development is considered to stem from its high protein content (60.6%) and nutritional value. Results have shown enhanced body weight gain (2.7%), better feed conversion ratio (lowered by 2.8%), meat colour and breast muscle weight (20.1%) in CLV-supplemented chicks compared to control birds (control breast weight 19.1%). Additionally, a significant decrease in drip loss (2.26%) from breast muscle was observed with CLV supplementation and levels of blood total protein, albumin, and high-density lipoprotein (HDL) cholesterol significantly increased (P<0.05), while the levels of liver enzymes indicative of oxidative damage (alanine aminotransferase, ALT) decreased by 23.2%, indicating better liver function. In terms of immunity, blood lymphocytes were increased in broilers fed a diet supplemented with liquid CLV (17.9 x 103/µl) compared with birds supplemented with dry CLV (13.5 x 103/µl). Additionally, the levels of IgA, IgG, and IgM were elevated by 29.7%, 69.1%, and 32.3%, respectively, in broilers that consumed feed containing CLV. Similarly, the intestinal diversity and abundance of Lactobacillus spp. were significantly increased (9.9 ± 1.88 and 8.99 log10 CFU/g, respectively) by dietary supplementation with liquid CLV compared to that in non-treated chicks (8.7 ± 1.22 and 8.51 log10 CFU/g, respectively). Energy digestibility was increased significantly by 1.29% in CLV-treated chicks compared to the control chicks. This review highlights the findings associated with the utilisation of CLV biomass as a feed supplement and its effect on broiler growth and health.